The Effect of Prior Comparison MRI on Interpretive Performance of Screening Breast MRI. Issue 1 (3rd January 2020) - Burk, Kristine S; Edmonds, Christine E; Mercaldo, Sarah F; Lehman, Constance D; Sippo, Dorothy A
Abstract: Objective: To evaluate the effect of prior comparison MRI on interpretive performance of screening breast MRI. Methods: After institutional review board approval, all screening breast MRI examinations performed from January 2011 through December 2014 were retrospectively reviewed. Screening performance metrics were estimated and compared for exams with and without a prior comparison MRI, using logistic regression models to adjust for age and screening indication (BRCA mutation or thoracic radiation versus breast cancer history versus high-risk lesion history versus breast cancer family history). Results: Most exams, 4509 (87%), had a prior comparison MRI (incidence round), while 661 (13%) did not (prevalence round). Abnormal interpretation rate (6% vs 20%, P < 0.01), biopsy rate (3% vs 9%, P < 0.01), and false-positive biopsy recommendation rate per 1000 exams (21 vs 71, P < 0.01) were significantly lower in the incidence rounds compared to the prevalence rounds, while specificity was significantly higher (95% vs 81%, P < 0.01). There was no difference in cancer detection rate (CDR) per 1000 exams (12 vs 20, P = 0.1), positive predictive value of biopsies performed (PPV3) (35% vs 23%, P = 0.1), or sensitivity (86% vs 76%, P = 0.4). Conclusion: Presence of a prior comparison significantly improves incidence round screening breast MRI examination performance compared with prevalence round screening. Consideration should be given to updating the BI-RADS breast MRI screening benchmarks and auditing prevalence and incidence round examinations separately.